Agronomy research in the Asian cassava network: Towards better production without soil degradation - Howeler, Reinhardt H. (International Center for Tropical Agriculture, 1995)
Since 1987 cassava agronomy research has been conducted by scientists from national cassava programs in Asia in collaboration and with small financial assistance from the CIAT cassava program. This paper summarizes and pulls together the results obtained, mainly corresponding to the period of 1490 to 1993. Research on cultural practices concentrated on determining the best time of planting and harvest, optimum planting methods and plant spacing as well as intercropping systems that increase farmers' financial returns. Planting cassava stakes in a vertical or inclined position generally increased yields compared with horizontal planting, but differences were not large and depended to some extent on the variety and on soil moisture conditions during planting. Vertical planting always resulted in quicker sprouting and canopy formation, which helps to reduce weed competition and erosion. Among various intercropping systems used in Asia, the interplanting of cassava with peanuts usually produced highest net incomes. A normal square planting arrangement often produced higher total net incomes than the wide-row or double-row arrangements. Long-term fertility trials have now been conducted for 3-5 years in nine locations in four countries. Significant responses to N were observed in seven locations and to P and K in four locations each. Responses to fertilizer application, especially to that of K, have been increasing over time. Only in Hung Loc Centre in south Vietnam no significant responses to fertilizer application were observed even after three years of continuous cropping. In most other locations the combined application of N, P and K more than doubled cassava yields. Erosion control trials have been conducted in 12 locations in six countries. The most effective practices to reduce erosion varied somewhat among locations, but generally in cluded contour ridging, closer plant spacing, fertilizer application, mulching and reduced tillage. Other practices, such as the planting of leguminous tree hedgerows, grass contour barriers or intercropping, will have long-term benefits in terms of erosion control, soil fertility maintenance and improving soil moisture conditions. Since the effect of these practices are rather site-specific and depend to a great extent on the socio-economic conditions of farmers,the choice of the best components of the technology, aimed at increasing farmers' income while preventing soil degradation, will need to be done on farmers' fields and through more active farmer participation in the research.